The fundamental beliefs held by individuals living with HIV and university students during the challenges posed by the second wave of the COVID-19 pandemic in Russia - V. V. Titova; V. I. Rozhdestvenskiy; I. A. Gorkovaya; D. O. Ivanov; Y. S. Aleksandrovich (European Psychiatry, 2024)
Introduction Baseline beliefs, as conceptualized by R. Janoff-Bulman in her cognitive theory of mental trauma, represent an inherent internal framework that shapes how individuals perceive and assess traumatic events. It is widely acknowledged that the pandemic has had a profound impact on the global economy and the living conditions of individuals. Consequently, it is reasonable to assume that during a pandemic, one’s ability to adapt to these altered circumstances is influenced by their foundational beliefs. Consequently, exploring these fundamental beliefs in two at-risk groups, namely university students and individuals with confirmed HIV, becomes a subject of significant interest.